Dampak pariwisata terhadap pencemaran air danau batur kabupaten bangli - Arik Agustina; Aprinica, Ni Putu Isha (Jurnal Ilmiah Hospitality Management, 2022)
This study aims to determine the impact of tourism on water pollution in Lake Batur. This study uses a qualitative descriptive analysis method. The samples taken include 5 points on Lake Batur which represent tourism locations on Lake Batur, namely the pier, restaurants, tourist attractions in Terunyan Village, hot spring attractions and the middle of the lake. Collecting data using observation methods, laboratory test methods and documentation studies. The research begins with direct observation to 3 key informants who can represent the condition of tourism in Lake Batur, namely the surrounding community, business and visitors. Furthermore, water sampling in Lake Batur and continued with laboratory testing for parameters of pH, biological oxygen demand (BOD), chemical oxygen demand (COD), oil and fat. Next is a documentation study on the situation and condition of Lake Batur and the last is collecting secondary data as supporting data. Furthermore, the data were analyzed de qualitatively to determine the impact of tourism potential on the water quality of Lake Batur. Based on the results of laboratory testing, Lake Batur is polluted in the restaurant and pier area. The restaurant area is characterized by high BOD parameters, while the pier area is characterized by high COD parameters. Based on this, it can be seen that tourism has an impact on increasing the value of pollutants in the waters of Lake Batur. Berdasarkan hasil pengujian laboratorium Danau Batur mengalami pencemaran pada daerah restoran dan dermaga. Pada daerah restoran ditandai dengan tingginya parameter BOD sedangkan daerah dermaga ditandai dengan tingginya parameter COD. Berdasarkan hal tersebut dapat dilihat bahwa pariwisata memberikan dampak terhadap peningkatan nilai pencemar pada perairan Danau Batur